Assessment the requirement of supply logistics processes improvement - Yangyozov, Petko; Dimitrova, Adile; Dimitrov, Ivan; Янгезов, Петко; Димитрова, Аділь; Димитров, Іван (Харківський національний автомобільно-дорожній університет, 2017)
In the present paper a method has been presented, through which it can be determining the requirement of improvement of supply logistics’ processes in the organization. The need for developing and implementation of this method is revealed. Also the essence of functioning of the method is represented. It can be described as a process which passes through three main stages. Each stage is built of several steps. At first stage explanation how the comparison between the set forth goal of improvement and the actual state of the current logistics processes is made. The formulas through which it can be calculated coefficients of „efficiency of maximized measures” and coefficients of “efficiency of minimized measures” are described. Methodology of calculating the coefficient of overall efficiency of the supply logistics, coefficient of single-dimension efficiency of the supply logistics and coefficient of multi-dimension efficiency of the supply logistics which are necessary for determining the general requirement of improvement are reviewed. Next stage is based on assessment the efficiency of sub-processes which build up supply logistics’ processes. Second stage starts only after the need of optimization on first stage is established. The explanation, how the comparison between targets subrocesses and their corresponding real subprocesses are performed. Coefficients and methodology of calculation of the “absolute goal” for improvement are discussed, through which the requirement of supply logistics subrocesses improvement is ascertained. In the third stage a few steps are presented, through which it can determine the priority of improvement of each supply logistics sub-process in the organization. The explanation, how the comparison between targets sub-processes and their corresponding real sub-processes are performed. Coefficients and methodology of calculation of the “absolute goal” for sub-process improvement in single and in all measurements are introduced.
Оцінка вимог покращення процесів постачання логістики
Keywords: supply logistics; supply logistics’ process; supply logistics’ sub-process; optimization; requirement of improvement; methodology; логістика поставок; процес логістики поставок; підпроцес логістики поставок; оптимізація; вимоги поліпшення; методологія; 658.7.011.1: 658.512.3